Emotion regulation improvement through short-term psychodynamic psychotherapy: a case report - Karisma Dewi Puspasari (Jurnal Konseling dan Pendidikan, 2025)
This study employed a qualitative single-case study design to examine the effectiveness of short-term psychodynamic psychotherapy (STPP) in improving emotion regulation in a young adult client with a history of mother–child relational conflict. The participant was a 24-year-old woman experiencing emotional instability associated with unresolved childhood relational trauma. Data were collected through structured observation, in-depth interviews, psychological tests, and standardized questionnaires administered before and after the intervention. Observation and interviews were used to explore emotional patterns and relational dynamics, while psychological tests and questionnaires provided measurable indicators of emotion regulation and parent–child relationship quality. The primary focus of the intervention was emotion regulation, while mother–child relational problems were treated as contributing background factors rather than the main treatment target. Data analysis was conducted by comparing pre- and post-intervention assessment results and integrating qualitative changes observed across therapy sessions. The intervention consisted of 16 sessions of STPP.The results indicated measurable improvements in emotion regulation and perceived parent–child relationship quality, supported by increased post-intervention assessment scores and observable behavioral changes, including improved emotional control, more adaptive emotional responses, and improved sleep patterns. This study contributes to the limited literature on the application of STPP for emotion regulation difficulties in young adults with relational trauma histories. However, findings are limited by the single-case design and reliance on short-term outcome measures. Further research using comparative or longitudinal designs is recommended to strengthen generalizability.